Isolation and Structural Characterization of Degradation Products of Aceclofenac by HPLC, HRMS and 2D NMR - Guduru, Santhosh; Karun Mutha, V.V.S.R.N. Anji; Vijayabhaskar, B.; Kaliyaperumal, Muralidharan; Korupolu, Raghu Babu; Bonige, Kishore Babu; Rumalla, Chidananda Swamy (Asian Journal of Chemistry, 2019)
The stability of aceclofenac under stress conditions was assessed to identify the degradation products. So, it was subjected to stress conditions like acid, base and oxidation, according to ICH guideline Q1A (R2). One degradation product formed when the drug was subjected to acid stress. Three degradation products were formed during the basic stress condition. The drug substance was found to be stable to oxidative stress. The degradants formed during the stress were separated on a C-18 column using gradient preparative HPLC elution. The only product (DP-2) formed during the acid stress and this one is same as of one of the three degradation products (DP-1, DP-2, DP-3) were formed during base stress. 1D and 2D NMR spectra and mass spectral analysis supported the proposed structures for the products. The products DP-2 and DP-3 have been reported earlier but this is the first report of product DP-1 as a degradation product of aceclofenac.